J. Endzelins and Lithuanian Folk Songs - Zinkevičius, Zenonas (Literatūra, 1973)
The article deals with a Latvian translation of two Lithuanian folk songs from the collection of G.M.F. Nesselmann, which were translated by J. Endzelins in 1894.
Keywords: -